AB0867 Axial spondyloarthritis posture assessment using inertial sensors. (12th June 2018) - Garrido-Castro, J.L.; Concha-Aranda, I.C.; Gardiner, P.; Machado, P.M.; Williams, J.; Collantes-Estevez, E.; ,
Abstract : Background: Axial Spondyloarthritis (axSpA) often causes spinal deformity in patients, most commonly a flexed kyphotic posture. In the early stages a flattening of the lumbar spine or reduced lordosis may become apparent. Kyphosis of the thoracic and cervical spine is also common in severe cases, resulting in an increased 'tragus to wall distance' as clinically assessed in the BASMI score. No other measurement related to posture is routinely recorded in clinical practice. Inertial Measurement Units (IMU) is a new technology that can measure angles of anatomical regions where the sensor is located. Objectives: To compare the spinal curvature of axSpA and healthy individuals to analyse if there are any significant differences between them and to correlate these with conventional assessment variables. Methods: 20 axSpa patients and 20 healthy age, BMI and sex matched controls, were recruited. An IMUs system (ViMove©) was used to obtain angles at key points along the spine. Sensors were located at Pelvis, L1, T3 and occiput (figure 1). Calibrated angles for all the participants where obtained with the subject in quiet standing position looking to a point in front of her/him. PRO questionnaires (only patients) and metrology for axSpA (both groups) were also assessed. ROM for cervical and lumbar spine was also measured using IMUs. Results: Greater values of posture angles were obtained in healthy controls. Despite this, differences where significant (p<0.05) only for Lordosis and Cervical Posture. Lordosis angle shown a good correlation with mobility measured by Schöber and by IMU system, especially for flexion movements. Pelvis angle correlates better than L1 angle with all mobility variables. For cervical angles, occiput angle appears to be the best indicator for functional assessment. Thoracic angle is very similar between patients and healthy subjects. Figure represents the location of sensors with mean angles obtained by healthy group and the worst patient of axSpA group. Conclusions: IMU based sensors are a useful new tool for the assessment of axSpA patients. This is the first formal evaluation of posture in axSpA and seems to be a promising tool in the functional evaluation of axSpA patients. More studies (reliability, feasibility, sensitivity to change, etc.) are needed for validating these measures. Acknowledgements: This study has been funded by FOREUM, University of Cordoba Research Program and Junta de Andalucía (CS-S0029/2016). Disclosure of Interest: None declared